Predicting the likelihood of venous leg ulcer recurrence: The diagnostic accuracy of a newly developed risk assessment tool. Issue 5 (13th March 2018) - Finlayson, Kathleen J.; Parker, Christina N.; Miller, Charne; Gibb, Michelle; Kapp, Suzanne; Ogrin, Rajna; Anderson, Jacinta; Coleman, Kerrie; Smith, Dianne; Edwards, Helen E.
Abstract : The aim of this study was to validate a newly developed tool for predicting the risk of recurrence within 12 months of a venous leg ulcer healing. Performance of the tool to predict recurrence within a 12‐month period was assessed using Area Under the Receiver Operating Characteristic Curve (AUC) analysis. Multi‐site retrospective and prospective longitudinal studies were undertaken to validate a risk assessment tool for the recurrence of venous leg ulcers within 12 months. In the retrospective study ( n = 250), 55% of venous leg ulcers recurred within 12 months, and the risk assessment total score had excellent discrimination and goodness of fit with an AUC of 0.83 (95% CI, 0.76‐0.90, P < .001). The prospective study ( n = 143) observed that 50.4% ( n = 63) of venous leg ulcers recurred within 12 months of healing. Participants were classified using the risk assessment tool as being at low risk (28%), moderate risk (59%), and high risk (13%); the proportion of wounds recurring at 12 months was 15%, 61%, and 67% for each group, respectively. Validation results indicated good discrimination and goodness of fit, with an AUC of 0.73 (95% CI, 0.64‐0.82, P < .001). Validation of this risk assessment tool for the recurrence of venous leg ulcers provides clinicians with a resource to identify high‐risk patients and to guide decisions on adjunctive, tailored interventions to address the specific risk factors to decrease the risk of recurrence.